2008
DOI: 10.1007/s00114-008-0446-0
|View full text |Cite
|
Sign up to set email alerts
|

Keeping the blood flowing—plasminogen activator genes and feeding behavior in vampire bats

Abstract: The blood feeding vampire bats emerged from New World leaf-nosed bats that fed on fruit and insects. Plasminogen activator, a serine protease that regulates blood coagulation, is known to be expressed in the saliva of Desmodus rotundus (common vampire bat) and is thought to be a key enzyme for the emergence of blood feeding in vampire bats. To better understand the evolution of this biological function, we studied the plasminogen activator (PA) genes from all vampire bat species in light of their feeding trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“… Vampire bats ( Desmodus rotundus ) are obligate blood feeders that have evolved specialized systems to suit their unique sanguinary lifestyle 13 . Chief among such adaptations is the ability to detect infrared radiation as a means of locating hot spots on warm-blooded prey.…”
mentioning
confidence: 99%
“… Vampire bats ( Desmodus rotundus ) are obligate blood feeders that have evolved specialized systems to suit their unique sanguinary lifestyle 13 . Chief among such adaptations is the ability to detect infrared radiation as a means of locating hot spots on warm-blooded prey.…”
mentioning
confidence: 99%
“…Plasminogen activators have been purified from the venomous snake, Trimeresurus stejnegeri [44] and from the saliva of common vampire bat, Desmodus rotundus [10], [45]. In vampire bats, plasminogen activator is thought to be a key enzyme that plays a crucial role in the maintenance of the flow of blood during the feeding process [46] and snake-venom plasminogen activator is associated with the pathogenesis of envenomation rendering the blood incoagulable [44]. Maintenance of hosts' blood fluidity at the site of biting is also very critical for the development of blood pool and subsequent blood feeding, and eventually for the survival of ixodid ticks.…”
Section: Discussionmentioning
confidence: 99%
“…Upon analysis, both fecal samples showed that pig and chicken blood had been ingested, indicating feeding flexibility in D. youngi. Like D. rotundus, D. youngi saliva also has a protease that greatly slows mammalian blood coagulation (Tellgren-Roth et al 2009). However, it is known that D. youngi has difficulty digesting high amounts of dry matter from mammal's blood (Coen 2002).…”
Section: Discussionmentioning
confidence: 99%